STUDI GAYA DESAIN PADA INTERIOR PUSAT KEBUDAYAAN PRANCIS (CCCL) DI SURABAYA - Latief, Luciana (Institute of Research and Community Outreach - Petra Christian University, 2009)
The French Cultural Center (CCCL) Surabaya is a building that has a high artistic value of architecture. Because this building was founded in the early 20th century, a period that coincided with the transition from the design style of neo classical to modern, the style used is also very varied. The analysis results show a combination of styles including: Dutch Colonial, Empire Style, Art & Craft, Art Nouveau, Amsterdam School, and the Nieuwe Bowen. Besides a combination of styles, the functional values and meanings are also applied to the interior elements.